2016
DOI: 10.3109/00016489.2015.1129068
|View full text |Cite
|
Sign up to set email alerts
|

Sialolithiasis is associated with nephrolithiasis: a case-control study

Abstract: Out of 3864 sampled patients, 165 (4.27%) had prior nephrolithiasis. Using Chi-square test, it was found that there was a significant difference in the prevalence of prior nephrolithiasis between the cases and controls (10.25% vs 2.28%, p < 0.001). Moreover, by conditional logistic regression analysis, the odds ratio of prior nephrolithiasis for cases was 4.74 (95% CI = 3.41-6.58, p < 0.001) when compared to controls after adjusting for monthly income, geographic location, urbanization level of residence, diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 11 publications
1
24
0
1
Order By: Relevance
“…Smoking and alcohol consumption were the most commonly performed social habits in patients with sialolithiasis. The association of sialolithiasis with smoking has been reported in several previous studies [1,9,10,12,13]. However, we could not find any study evaluating the correlation between alcohol consumption and sialolithiasis.…”
Section: Introductionmentioning
confidence: 55%
“…Smoking and alcohol consumption were the most commonly performed social habits in patients with sialolithiasis. The association of sialolithiasis with smoking has been reported in several previous studies [1,9,10,12,13]. However, we could not find any study evaluating the correlation between alcohol consumption and sialolithiasis.…”
Section: Introductionmentioning
confidence: 55%
“…These results indicate 337 338 339 340 341 342 343 344 345 346 347 348 349 350 351 352 353 354 355 356 357 358 359 360 361 362 363 364 365 366 367 368 369 370 371 372 373 374 375 376 377 378 379 380 381 382 383 384 385 386 387 388 389 390 391 392 393 that a reduced salivary citrate concentration and increased pH could increase calcium deposition by way of the same mechanisms seen in renal stone formation. In support of the hypothesis of a connection between renal and salivary stone formation, a recent large case-control study of 3,864 patients in Taipei by Wu et al 26 reported a strong association of sialolithiasis with a history of nephrolithiasis, with an adjusted odds ratio of 4.74. If excess calcium from the oral environment assists in the formation of sialoliths, perhaps our patient's daily oral intake of calcium carbonate (1,000 mg) in a chewable form might have played a role in her salivary gland stone development.…”
Section: Discussionmentioning
confidence: 90%
“…First, she had no other known risk factors for sialolithiasis, including no history of diabetes, chronic renal disease, tobacco use, hypoparathyroidism, dehydration, poor oral hygiene, gout, or previous trauma to the salivary glands. 26 Second, the patient presented with cloudy urine with precipitate, suggesting decreased calcium solubility in excreted fluids. This change to the patient's urine occurred shortly after the initiation of the drug and reversed on its discontinuation.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have demonstrated associations between sialolithiasis and cholelithiasis as well as nephrolithiasis . Interestingly, it has long been reported that nephrolithiasis is associated with osteoporosis .…”
Section: Introductionmentioning
confidence: 96%
“…Our previous studies have demonstrated associations between sialolithiasis and cholelithiasis as well as nephrolithiasis. 7,8 Interestingly, it has long been reported that nephrolithiasis is associated with osteoporosis. [9][10][11][12][13][14] Little is known about the contribution of systemic predisposing factors to the development of sialolithiasis in the context of systemic calcium metabolism disorders, such as osteoporosis.…”
mentioning
confidence: 99%